The Ppraticality of Using Cloud Computing Services for Small and Medium Enterprises - Nair, Varun (2011)
Few years back, “cloud computing” was a buzz word in the IT industry with organizations and vendors contemplating the use of computing as a utility. Today, companies are gearing up for the eventual adoption of cloud. The report explores the use of cloud computing to satisfy the computing needs of Small and Medium Enterprises (SME), a sector which would immensely benefit from the cost advantage provided by cloud. The report identifies the technicalities in cloud, the need for cloud computing, various roles in the cloud, benefits and challenges of moving to cloud. The report also looks at the various trends in the emerging SME sector and factors affecting the IT readiness in SME. In the end the study concludes with some recommendations for SMEs and CSPs in order to have a mutually beneficial relationship from cloud.